Soil erosion and nutrient management in farming systems of the northern uplands of Vietnam - Hoang Van Phu; Mendoza, Teodoro C. (2003)
The predominant practice of 89% of farmers growing tillage-intensive annual crops such as upland rice or mixed annual crops was identified as the main factor causing massive soil erosion (more than 100 t ha-1 yr-1) and nutrient losses in the uplands of Dinh Hoa, Vietnam. The early growth of these crops and their insufficient canopy cover to the soil coincide with the peak rainy months of June to August. It was estimated that 15 cm of the topsoil in Dinh Hoa would be eroded in about 10 yr for areas grown to upland rice at slopes of 25°-29° or in only 4 yr at slopes of 40° or higher. Burning of crop and weed residues, as done by 55.7% of the farmers, also brought about nutrient losses in cropping systems involving peanut-sweet potato, cassava and sweet potato-corn. But for root crops (sweet potato-corn, peanut-sweet potato, and bean-sweet potato and cassava), the greatest loss in N and K occurred through the harvest of economic products. Topsoils and nutrients were projected to be retained up to 100 yr in cassava+peanut intercropping and in farms planted to perennial crops such as tea or mixed fruit orchard. This demonstrates that the economic, environmental protection and conservation goals of upland farming in Dinh Hoa are potentially achievable. But 60% of farmers were not aware that improper farming practices caused soil erosion (hence, nutrient loss). Information and guidance, credit support, improvement of rural infrastructure such as roads and provision of processing facilities could motivate farmers to shift to the planting of perennial high-value fruit trees. This cropping system would enable farmers to benefit from the unique subtropical climate of the uplands of Dinh Hoa in an environment-friendly way.
Keywords: Soil erosion; Upland farming